Selected letters of Dashiell Hammett 1921 - 1960 - Hammett, Dashiell 1894-1961 (Counterpoint, 2001)
"Here is a volume that generations of readers have longed for - the first-ever selection from the letters of Dashiell Hammett, the onetime private detective who, in five astonishing books written between 1927 and 1933, invented the modern American crime novel. Hammett was not only the founding member of the hardboiled school, he also was its greatest practitioner, and even after Chandler and all the rest, his body of work remains the solid-gold standard. The best of his work is literature - without the quotation marks."--BOOK JACKET.